Receptions and Official Celebrations in Baghdad During The Late Abbasid Era (550-656 H /1155-1258 Ad) - Mohammed Abdullah Alqadahat (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
The late Abbasid era witnessed a successful political experience, culminating in the restoration of the Abbasid Caliphate institution’s prestige that disappeared for a long time. The caliphs of this era were keen to keep that achievement. They restored the ceremonies that used to be performed during the days of the Caliphate’s Golden Age. One of those ceremonies was the reception of distinguished visitors such as sultans, princes, and messengers who arrived in Dar Al-Khilafah. Those ceremonies followed a regular pattern and were under the supervision of an institution associated with Diwan Al-Khilafah known as Dar Atashreefat (House of Ceremonies). Reception ceremonies began from the moment of the arrival of the Caliph’s guests to the outskirts of Baghdad, where the Caliphal procession stood waiting to receive those guests, then accompanied them to Dar Al-Khilafah. At the same time, Dar Atashreefat arranged everything related to the visit; preparing the house for residency, the guest’s visit to Dar Al-Khilafah to be honored by the meeting of the Caliph, concluding the visit and bidding farewell to the guest.